2020
DOI: 10.1155/2020/2435793
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Detection and Classification of Road, Car, and Pedestrian Using Binocular Cameras in Traffic Scenes with a Common Framework

Abstract: In order to solve the problems of traffic object detection, fuzzification, and simplification in real traffic environment, an automatic detection and classification algorithm for roads, vehicles, and pedestrians with multiple traffic objects under the same framework is proposed. We construct the final V view through a considerate U-V view method, which determines the location of the horizon and the initial contour of the road. Road detection results are obtained through error label reclassification, omitting p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…YOLOv2 [20], an enhanced version, incorporates anchor boxes, and K-means clustering, enhancing training models. Efficient proposes a compound scaling strategy for elevated object detection performance, while RetinaNet introduces a focal loss function to mitigate class imbalance issues [21].…”
Section: Related Workmentioning
confidence: 99%
“…YOLOv2 [20], an enhanced version, incorporates anchor boxes, and K-means clustering, enhancing training models. Efficient proposes a compound scaling strategy for elevated object detection performance, while RetinaNet introduces a focal loss function to mitigate class imbalance issues [21].…”
Section: Related Workmentioning
confidence: 99%
“…Zhang, Xiao, Coifman, and Mills (2020) proposed a centroid-based tracking method and a refining module to track vehicles and improve speed estimations. Song, Yao, Ju, Jiang, and Du (2020) proposed a framework to detect roads, pedestrians, and vehicles using binocular cameras. In another multi-modal research, thermal sensor data is fused with the RGB camera sensor, leading to a noise-resistant technique for traffic monitoring (Alldieck, Bahnsen, & Moeslund, 2016).…”
Section: Road-user Detection Researchmentioning
confidence: 99%
“…Adrian et al [8] showed multiple representations of the disparity image and uvθ-disparity to achieve obstacle detection. Song et al [9] presented obstacle detection using a considerate uv-disparity that uses a refined v-disparity for accurate road segmentation. These approaches are equally applicable in a system that helps visually impaired persons [10] because of the similarities in the motion characteristics between humans and AGVs.…”
Section: Literature Survey and Motivation Of The Workmentioning
confidence: 99%